Health region development from the perspective of system theory – An empirical cross-regional case study. (January 2015) - Volgger, Michael; Mainil, Tomas; Pechlaner, Harald; Mitas, Ondrej
Abstract: Governments are increasingly establishing health regions to deal with current challenges of public health service. These regions are seen as instruments to balance public and private stakeholders, and offer health care to regional citizens as well as to medical/health tourists. However, it is still unclear how the development of such health regions as well as their governance may be conceptualized. We apply Luhmann's system theory approach in the context of a cross-regional case study that compares health region developments in the Autonomous Province of Bolzano–South Tyrol (Italy) with particular regard to the Eastern Dolomites and in the province of Zeeland (the Netherlands). We suggest that Luhmann's system theory provides a useful set of criteria to evaluate and judge health region development. Fully developed health regions can be understood as auto-poietic systems. By emphasizing programs, personnel, and communication channels, these case studies illustrate the suitability of the system theory toolset to analyze the governance and spatial embeddedness of health regions. Additionally, the study contributes to literature by indicating that health regions are closely related to identity issues and to decision making in regions. Highlights: We explore the applicability of system theory to health region development. Health region governance depends on programs, personnel and communication channels. We compare the two European regions of Zeeland and South Tyrol/Bolzano. Health regions appear as mechanisms in identity politics.